2022
DOI: 10.48550/arxiv.2205.09569
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Provably Precise, Succinct and Efficient Explanations for Decision Trees

Abstract: Decision trees (DTs) embody interpretable classifiers. DTs have been advocated for deployment in high-risk applications, but also for explaining other complex classifiers. Nevertheless, recent work has demonstrated that predictions in DTs ought to be explained with rigorous approaches. Although rigorous explanations can be computed in polynomial time for DTs, their size may be beyond the cognitive limits of human decision makers. This paper investigates the computation of δ-relevant sets for DTs. δ-relevant se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…There is recent initial work on the complexity of computing probabilistic explanations [312,313], where the name probabilistic prime implicants is used. Following more recent work [169,170,172], we will use the term(s) (weak) probabilistic abductive explanations ((W)PAXp's).…”
Section: Probabilistic Explanationsmentioning
confidence: 99%
See 4 more Smart Citations
“…There is recent initial work on the complexity of computing probabilistic explanations [312,313], where the name probabilistic prime implicants is used. Following more recent work [169,170,172], we will use the term(s) (weak) probabilistic abductive explanations ((W)PAXp's).…”
Section: Probabilistic Explanationsmentioning
confidence: 99%
“…Recent work [312,313] established that, for binary classifiers represented by boolean circuits, it is NP PP -complete to decide the existence of a set X ⊆ F , with |X | ≤ k, such that (20) holds. Despite this unwieldy complexity, it has been shown that for specific families of classifiers [170,172], it is computationally easier and practically efficient to compute (approximate) subset-minimal sets such that (20) holds. Concretely, instead of (2), we will instead consider:…”
Section: Problem Formulationmentioning
confidence: 99%
See 3 more Smart Citations